‘[E]very word he says to me enters my heart and has a new meaning for me’: The Soundscape in George Eliot’s Janet’s Repentance - Lilia Miroshnychenko (Cahiers Victoriens et Edouardiens)
To pursue the theme of soundscape (to use Murray Schafer’s term) in George Eliot’s Janet’s Repentance, this paper will successively address more specific topics: the forms of sound representations, the sound as an articulation of the social, the affinity of sound and sympathetic resonance. It will also look at how critical hearing and speaking are to the crafting of the narrative and characterisation.